2012
DOI: 10.1002/ccd.24332
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aortic valve calcification on the outcome of transcatheter aortic valve implantation: Results from the prospective multicenter German TAVI registry

Abstract: Our results of a real-world registry suggest that the extent of aortic valve calcification does not influence the success or procedural outcome significantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…Importantly, neither regional calcification nor asymmetry differed significantly between patients that met the 30‐day VARC‐2 composite endpoint and those that did not, suggesting that early safety is not directly affected by the degree or distribution of calcification. This is in agreement with findings from the multicenter German TAVI registry, which also found calcification to be unrelated to the frequency of death, stroke, and MI at 30 days . Also consistent with the literature are the higher frequencies of clinically relevant mitral regurgitation, mitral stenosis, and PVL in patients experiencing poorer outcomes post‐TAVI, supporting the validity and pertinence of our data.…”
Section: Discussionsupporting
confidence: 92%
“…Importantly, neither regional calcification nor asymmetry differed significantly between patients that met the 30‐day VARC‐2 composite endpoint and those that did not, suggesting that early safety is not directly affected by the degree or distribution of calcification. This is in agreement with findings from the multicenter German TAVI registry, which also found calcification to be unrelated to the frequency of death, stroke, and MI at 30 days . Also consistent with the literature are the higher frequencies of clinically relevant mitral regurgitation, mitral stenosis, and PVL in patients experiencing poorer outcomes post‐TAVI, supporting the validity and pertinence of our data.…”
Section: Discussionsupporting
confidence: 92%
“…It remains unclear whether aortic valve calcification affects clinical outcomes after TAVI or not. The German TAVI‐registry showed that the extent of aortic valve calcification does not influence the success or procedural outcome significantly . In this German TAVI‐registry, 80.8% of patients were treated by CoreValve implantation and the assessment of aortic valve calcification was performed visually by the investigator.…”
Section: Discussionmentioning
confidence: 99%
“…It appears teleological that the degree of valvular calcification magnifies this risk. Staubach et al [2] have not confirmed this relationship. Similarly, Erkipac et al [5] in a comprehensive review of the published literature surrounding the outcome of PPI following TAVI were not able to identify aortic valve characteristics predictive of the need for PPI.…”
mentioning
confidence: 86%
“…In this issue of Catheterization and Cardiovascular Interventions, Staubach et al examine the effect of aortic valve calcification on TAVI outcome in a prospective multicenter German registry [2]. In this study, the investigators analyzed the clinical outcomes of 1,365 patients undergoing TAVI, qualitatively categorizing their patients into three groups based on the degree of aortic valve calcification (mild, moderate, and severe).…”
mentioning
confidence: 98%
See 1 more Smart Citation